The effects of spring to the suspension system / Peter Gerald Mojuli, Mohammad Hazrin Abdol Rahman and Zulhairizam Zulkapli - Mojuli, Peter Gerald; Abdol Rahman, Mohammad Hazrin; Zulkapli, Zulhairizam (2002)
The title of our final project is" The effects of spring to the suspension system". The purpose of this study shall be concerning with the stiffness of coil spring when in original length or after modified. Generally, in this project we fabricated the test set-up for testing coil spring of vehicle and loads, which will be applied, to it. In future, students working in this set-up will be able to find the performance of coil spring by applying different loads with relationship to the spring displacement. By this research, we can know the ability of coil spring by following the duration of uses and how much capability of load that can be loaded. By doing this research, we gained a lot of experience on spring stiffness due to load applied when the spring is in standard or modified length.